Revista Recreio (1969-1982): Leituras infantis sobre princesas, vovós e sacis - Silva, Tatiana Mortosa Faria (2024)
This paper takes Recreio magazine in its first phase (1969-1982) as a research object and as a source for writing the history of children's education. In this way, it seeks to problematize the following questions: To what extent does Recreio respond to the demands of a given time/space? What content did the children of those times read at playtime? Do the editions present a symbolic advance in relation to the historically constructed images of girls, grandmothers and blacks in the period? As an object of research, it reviews the scarce bibliography on the newspaper and tries to situate it as one of the most important communication vehicles for the education of children in the second half of the 20th century in Brazil. It discusses the "magazine-toy" hybridity, understanding Recreio as a successful product of Editora Abril, the most important and profitable publishing house in the country at the time. At the same time, by taking Recreio as a source for writing the history of children's education, it reviews the bibliography on the emergence of the theme of "childhood" in the Western world and, finally, highlights some of the teachings observed in the issues analyzed. Thus, throughout the research, we considered Recreio as a cultural artifact, observed in the light of the assumptions presented by Chartier (1998; 2009) and Burke (1989; 2000; 2005). We used the study of Cultural History to understand the magazine, and other authors, such as Darnton (1986), Luca (1998; 2006), Campos (2009; 2012) and Galvão and Moreira (2021), among other historians of printed matter and education, anchor the discussions held. Keywords: Recreio Magazine; Children's Prints; Children.